Body size : the structure and function of aquatic ecosystems - Hildrew, A. G.; Raffaelli, D. G. (Dave G.); Edmonds-Brown, Ronni; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Ecologists have long struggled to predict features of ecological systems, such as the numbers and diversity of organisms. The wide range of body sizes in ecological communities, from tiny microbes to large animals and plants, is emerging as the key to prediction. Based on the relationship between body size and features such as biological rates, the physics of water and the amount of habitat available, we may be able to understand patterns of abundance and diversity, biogeography, interactions in food webs and the impact of fishing, adding up to a potential 'periodic table' for ecology. Remarkable progress on the unravelling, describing and modelling of aquatic food webs, revealing the fundamental role of body size, makes a book emphasising marine and freshwater ecosystems particularly apt. In this 2007 book, the importance of body size is examined at a range of scales that will be of interest to professional ecologists, from students to senior researchers.
The metabolic theory of ecology and the role of body size in marine and freshwater ecosystems / James H. Brown, Andrew P. Allen and James F. Gillooly -- Body size and suspension feeding / Stuart Humphries -- Life histories and body size / David Atkinson and Andrew G. Hirst -- Relationship between biomass turnover and body size for stream communities / Alexander D. Huryn and Arthur C. Benke -- Body size in streams : macroinvertebrate community size composition along natural and human-induced environmental gradients / Colin R. Townsend and Ross M. Thompson -- Body size and predatory interactions in fresh waters : scaling from individuals to communities / Guy Woodward and Philip Warren -- Body size and trophic cascades in lakes / J. Iwan Jones and Erik Jeppesen -- Body size and scale invariance : multifractals in invertebrate communities / Peter E. Schmid and Jenny M. Schmid-Araya -- Body size and biogeography / B.J. Finlay and G.F. Esteban -- By wind, wings or water : body size, dispersal and range size in aquatic invertebrates / Simon D. Rundle, David T. Bilton and Andrew Foggo -- Body size and diversity in marine systems / Richard M. Warwick -- Interplay between individual growth and population feedbacks shapes body-size distributions / Lennart Persson and André M. De Roos -- The consequences of body-size in model microbial ecosystems / Owen L. Petchey, Zachary T. Long and Peter J. Morin -- Body size, exploitation and conservation of marine organisms / Simon Jennings and John D. Reynolds -- How body size mediates the role of animals in nutrient cycling in aquatic ecosystems / Robert O. Hall, Jr. ... [et al.] -- Body sizes in food chains of animal predators and parasites / Joel E. Cohen -- Body size in aquatic ecology : important, but not the whole story / Alan G. Hildrew, David G. Raffaelli and Ronni Edmonds-Brown.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Aquatic animals -- Size; Aquatic ecology; Electronic books